The complete mitogenome sequence and organization of Parachaeturichthys polynema (Gobiiformes: Gobiidae) - Hanye Zhang; Qiqun Cheng (Mitochondrial DNA. Part B. Resources, 2023)
In this study, the complete mitochondrial genome of Parachaeturichthys polynema was reported. The mitochondrial genome was 16,620bp in length including 13 protein-coding genes, 23 tRNAs, 2 rRNAs, and a control region. The overall contents of A, T, G, and C were 28.56%, 26.34%, 16.22%, and 28.89%, respectively. Phylogenetic analysis of 18 species in the family Gobiidae showed that P. polynema was clustered into the subfamily Gobiinae. This information will contribute to future phylogenetic studies of P. polynema and Gobiidae.